أساليب المنافقين القولية في الكيد للدّعوة الإسلامية في سورة التّوبة - سرار, سليم; شواش, عادل (جامعة الوادي - University of Eloued, 2021)
من مظاهر عظمة القرآن الكريم وإعجاز نظمه وموضوعاته أنّ كلّ سورة من سوره قد انفردت بموضوعات كبرى بارزة عالجتها ببيان كنهها وأساليبها وغير ذلك، ومن سور القرآن الكريم التي انفردت بالحديث عن موضوع خطير يهدد كيان المجتمع المسلم وتماسكه من داخله؛ سورة التّوبة حيث أنّها من السّور المدنية التي تضمّنت الحديث على النّفاق والمنافقين وصفاتهم وأساليبهم وطرقهم في صدّ دعوة الإسلام. ومن هنا جاءت فكرة البحث وإشكاليتُه حيث يتساءل التّالي لسّورة التّوبة عن الطّرق القولية التي اعتمدها المنافقون في الكيد لدعوة الإسلام وصدّها، حتّى يتسنى له التنبّه لهذه الطّرق والحذر منها ثمّ في الأخير تحذير المسلمين منها وصدّها ومحاربتها، ولتحقيق ما تمّ ذكره انتظم هذا البحث في مقدمة ومتن وخاتمة. وخاتمة هذا البحث اشتملت على مجموعة من النّتائج أهمّها: أنّ المنافقين غاية جهدهم وأكبر همّهم هو محاولة القضاء على الدّعوة الإسلامية معتمدين في ذلك على أخبث الأساليب القولية وأشنعها. One of the manifestations of the greatness of the Qur'an and the miracle of its systems and topics is that each of its surahs has been singled out for major prominent topics that I have addressed with a statement of its nature, methods, etc. One of the walls of the Holy Quran, which is unique in talking about a serious issue that threatens the entity and cohesion of the Muslim society from within, is the Surat al-Tawba, which included talking about hypocrisy and hypocrites, their prescriptions, methods and ways to repel the call of Islam. Hence the idea of research and its problem, where the following asks the next to the repentance about the ways of saying that the hypocrites adopted in the malicious to call Islam and repel it, so that he can be aware of these methods and be ware of them and then in the end repel them and fight them and warn Muslims of them, and to achieve what was mentioned organized this research in the introduction, the two researchers and the conclusion. The conclusion of this research included a set of findings, the most important of which is that hypocrites are very hard-working and their biggest concern is to try to eliminate the Islamic da'wa, relying on the most sinister and heinous methods of words
مقال
Keywords: التّوبة؛ ; النّفاق؛ ; المنافقون؛ ; أساليب.; Surat Al-Tawbah; methods; the hypocrits